Grumpy groundhog - Wright, Maureen, 1961-; Haley, Amanda (Las Vegas, NV : Two Lions/Amazon Publishing, 2014)
It's Groundhog's Day, and everyone is gathered to find out if it's time for spring. But Groundhog does NOT want to leave his cozy bed in his cozy den. Will the townspeople be able to coax him outside to do his job?
Keywords: Groundhog Day -- Juvenile fiction; Woodchuck -- Juvenile fiction; Stories in rhyme